Characteristics and outcome of biopsy-proven malignant hypertension with severe kidney injury: A retrospective study - Satish Haridasan (Wolters Kluwer Medknow Publications, 2021)
Background: Although malignant hypertension begets multiple target organ damage, there is limited data on patients with severe renal injury and evident malignant hypertension in renal histopathology. Methods: We assessed the baseline demographic, histopathological findings and clinical outcomes in this retrospective analysis of patients with biopsy-proven malignant hypertension. Results: Thirty cases were analysed, the mean age of patients was 40 ± 11.5 years, 28 (93.3%) were males and the average systolic and diastolic blood pressures at hospitalisation were 197.04 ± 24.14 and 117.41 ± 18.31 mmHg, respectively. Severe retinopathy was seen in 10 (33.3%). The median eGFR at admission was 6.3 (IQR 4.4–9.15) mL/min and 21 (72.4%) needed dialysis. Nine (30%) cases with glomerular crescents were having the primary glomerular disease (7 IgAN, 1 C3 glomerulonephritis, 1 membranoproliferative glomerulonephritis) and 17 (56.6%) had thrombotic microangiopathy. Three-month ESRD free survival was 34.5% (n = 10) and the ESRD cohort had more incidence of dialysis requiring kidney injury at presentation (94.4% vs. 40% in the non-ESRD cohort). Patient survival at 1 year was 50%. Isolated malignant hypertension, differed from others with regard to lesser incidence of severe retinopathy, less glomerular sclerosis (29.61 ± 15.86 vs. 48.45% ± 30.78; P = 0.03), absence of crescents (P = 0.02), more incidence of tuft wrinkling (100% vs. 35%, P = 0.00) and total vessel occlusion (P = 0.02). Conclusion: Clinicopathologically, accelerated essential hypertension differs from hypertension of glomerular disease. Degree of kidney injury at presentation is risk predictor for long-term morbidity in malignant hypertension.